Influence of Process Operation on the Production of Exopolysaccharides in Arthrospira platensis and Chlamydomonas asymmetrica - Jung, Sun-Hwa; Zell, Niklas; Boßle, Fabian; Teipel, Ulrich; Rauh, Cornelia; McHardy, Christopher; Lindenberger, Christoph (Frontiers in Sustainable Food Systems, 2022)
Extracellular polysaccharides, or exopolysaccharides (EPS), are high–molecular weight sugar-based polymers expressed and secreted by many microorganisms. As host organisms, the functions of EPS are diverse, ranging from physical protection via biofilm formation, adhesion, and water retention, to biological functions that are not entirely understood such as viral attachment inhibition. Industrial applications of EPS can be found in food texture modification; for example, utilizing the hydrocolloidal properties of EPS for thickening and gelling purposes to improve food quality and texture. Over the last decade, biologically active EPS produced by microalgae have received attention for their potential as antiviral, antibacterial and antioxidative compounds and their resulting applications. However, relatively low yields and productivity are the limiting factors for full-scale industrial application. In this study, the well-known prokaryotic phototrophic microorganism Arthrospira platensis and the comparatively unknown eukaryotic unicellular green alga Chlamydomonas asymmetrica were used to evaluate the influence of different process parameters on EPS formation and productivity. In addition to the essential control variables (light and temperature), we also investigated the influence of operational techniques (batch and turbidostat). Although the two studied algae are differently affected by various parameters both microorganisms, the parameter light intensity was the most influential, leading to differences in EPS concentrations by a factor of 10, with the highest measured concentration for A. platensis of c_EPS=0.138 g L^(-1) at 180 µmol m-2 s-1 and for C. asymmetrica of c_EPS=1.2 g L^(-1) at 1429 µmol m-2 s-1. In continuous systems, the achieved EPS concentrations were lower compared to batch processes; however, slightly higher productivities were reached. Regardless of all screened process parameters, C. asymmetrica is the better production organism in terms of EPS concentrations and productivity.